Child health prioritisation in national adaptation policies on climate change: a policy document analysis across 160 countries - Zangerl, Kathrin; Hoernke, Katarina; Andreas, Marike; Dalglish, Sarah L.; Kelman, Ilan; Nilsson, Maria; Rocklöv, Joacim; Bärnighausen, Till; McMahon-Rössle, Shannon A. (The lancet child & adolescent health, 2024)
Integration of child-specific adaptation measures into health policies is imperative given children's heightened susceptibility to the health impacts of climate change. Using a document analysis method, we examined 160 national adaptation policies for inclusion of child-relevant measures and identified 19 child health-related adaptation domains. 44 (28%) of 160 countries' policies that were analysed failed to include any domains, 49 (31%) included at least one child-related domain, 62 (39%) included between two and six domains, and five (3%) included at least seven domains. Predominant domains among child-specific adaptation measures included education and awareness raising, followed by community engagement and nutrition. No country addressed children's direct needs in the domain of mental health. National adaptation policies tend towards overly simple conceptualisations of children across four major lenses: age, social role, gender, and agency. Limited inclusion of child-specific measures in national adaptation policies suggests insufficient recognition of and action on children's susceptibility to climate change effects.
Online verfügbar: 4. Juni 2024, Artikelversion: 17. Juni 2024
Gesehen am 03.02.2025